PIG (SUS SCROFA) VOCALIZATION ASSESSMENT AS AN INDICATOR OF ENERGY EXPENDITURE. - CORDEIRO, ALEXANDRA FERREIRA DA SILVA; NÄÄS, IRENILZA DE ALENCAR; DA SILVA, WAGNER TOMÉ; DE MOURA, DANIELLA JORGE (Revista Brasileira de Engenharia de Biossistemas, 2008)
In intensive pig production stressing managements such as weaning, teeth cutting and castrationmay reduce animals’ welfare status and lead to decrease in productive performance. Vocalizationis a useful tool to identify stressful conditions in swine production. The objective of this researchwas to quantify the energy expenditure of vocal expression of reared pigs, in distinct stressconditions. Pig vocalizations in seven conditions were analyzed: normal, with hunger, very hungry,with pain, very painful, with fear and with much fear. The sound signal capture was done using anelectret microphone positioned 1.0 m above the animals and a laptop where the signals weredigitalized by the sound hardware and recorded at a frequency up to 44,100 Hz. For analyzing therecorded signals the Matlab® environment and the software Audacity 1.3.0 were used. Vocalizationsound intensity was higher in stressful conditions. The energy of the vocal sound was 0.107 kcal/s for pigs in normal condition, increasing considerably as the animal reaches high intensity ofstress exposure, up to 7.602 kcal/s for pigs submitted to high pain. The duration of vocalizationwas also higher in stressful conditions, vocal expression related to pain and higher pain represented3.7 and 3.6 times more duration than those related to piglets in normal conditions. These resultsshowed that there is energy expenditure when the pig vocalizes and that this value increases asfunction of the stress exposure.